General versus local anesthesia for carotid endarterectomy: Special considerations - Nikolaos Patelis; Maria Diakomi; Anastasios Maskanakis; Konstantinos Maltezos; Dimitrios Schizas; Marianna Papaioannou (Saudi Journal of Anaesthesia, 2018)
Anesthesia for carotid endarterectomy (CEA), general or locoregional, has been an issue of debate in literature ever since the first Cochrane review in 1991. The largest available study on the subject, the GALA trial, has not shown any difference in patient's outcome – incidence of stroke and 30-day-mortality postsurgery. However, increasing evidence favors regional anesthesia as an independent factor of reduced morbidity after CEA. The advantages and disadvantages of general versus regional anesthesia for CEA have been well established. Cervical plexus blocks (CPBs) are safe and effective anesthetic techniques, but they may also present adverse effects that we must be aware of. Optimal cerebral function monitoring remains a problem to be solved. Cerebral oximetry may prove to be a reliable tool in predicting neurological impairment. This narrative review intends to highlight the latest implemented anesthetic modalities for CEA, including CPB under ultrasound guidance, and to outline the main limitations of general versus regional anesthesia. Following the appropriate anesthetic, modality necessitates a thorough preoperative consultation among the patient, the surgeon, and the anesthetist. The anesthetic plan should be made on an individual basis, taking into consideration patient's comorbidities and wish.